The Positive Link Between Self-Esteem and Consumptive Behavior Among Generation Z Shopee Users in Urban Indonesia - Ester Dwi Meliana; Susana Prapunoto (Universitas PGRI Yogyakarta, 2026)
This study examines the relationship between self-esteem and consumptive behavior among Generation Z users of the Shopee e-commerce platform in Cipondoh District, Tangerang City. Previous studies report inconsistent findings, with many emphasizing negative relationships in which low self-esteem drives impulsive or excessive consumption. Addressing this gap, the present study provides contextual evidence from a digitally intensive urban environment, where consumption functions as identity affirmation rather than emotional compensation. Using a quantitative cross-sectional design, data were collected from 407 Generation Z participants through accidental sampling. Self-esteem was measured with the Coopersmith Self-Esteem Inventory (CSEI), and consumptive behavior was assessed with the Consumer Orientation Scale. Spearman’s rank correlation analysis revealed a positive and significant relationship between self-esteem and consumptive behavior (r = .274, p < .01), indicating a low-strength correlation. This finding suggests that higher self-esteem is associated with stronger consumptive tendencies, particularly through symbolic self-expression on digital marketplaces. However, the cross-sectional design and accidental sampling limit causal inference and generalizability. Future research should employ longitudinal designs, include mediating variables such as social media use or fear of missing out (FoMO), and compare multiple e-commerce platforms. Keywords: consumptive behaviour, self-esteem, Z generation